Developing a satellite-based combined land degradation index for monitoring environmental change: A case study in Tana-Beles watershed, Upper Blue Nile, Ethiopia - Abeyou, Abeyou; Haddad, Mira; Alemayehu, Sintayehu; Govind, Ajit (Elsevier, 2023)
Land degradation is one of the most pressing environmental challenges due to its effect on the people and ecosystem. Early detection of land degradation could help to avoid further deterioration and work on reversing the trend. This would require an integrated approach combining indicators such as vegetation condition, soil health (i.e., soil salinity), and soil exposure (i.e., albedo) to characterize land degradation comprehensively. Therefore, this study aims at developing a satellite image-based combined land degradation index to monitor the spatial extent of land degradation in the Upper Blue Nile Basin, Ethiopia. In addition, the study also evaluates the environmental change associated with land degradation across the Tana-Beles watershed. The combined land degradation index (CLDI) was developed by integrating multiple indicators, including normalized vegetation Index (NDVI), salinity index (SI), and albedo, for two periods spanning between 1990 and 2000 (1990s) and 2010 to 2020 (2010s). The individual indicators were combined with Principal Component Analysis (PCA) by assigning weights to the individual indicators. The analysis indicated that, in the 2010s, the vegetation condition deteriorated over 98.5% of the study area, while soil salinity and albedo increased by 82% and 97% in the 1990s, respectively. The combined land degradation index developed with the PCA indicated in the 2020s a fraction of the study area ∼2% is extremely degraded, while 18%, 43%, 27%, and 10% of the site is strongly, moderately, slightly, and not degraded, respectively. Monitoring land degradation is important for countries like Ethiopia, where most of the county are occupied by semi-arid and arid climate zones.